Assessment of the Transport Complex in Providing Economic Spatial Development of the Territories - Rodchenko, V.; PrusSvidenska, Yu.; Svidenska, M.; Khripunova, D. (International Journal of Engineering and Technology, 2018)
The role of the transport component in ensuring economic development processes of the territories was considered. Works of many scientists wereÂ analyzed, systematized and generalized, it was discovered that the key task of forming a single economic space in Ukraine isÂ to overcome inter-territorial differentiation, spatial integration of territories, which provides the maximum intensive interaction of business entities of certain territories through all possible channels of communication. One of the key factors in such integration is transport. The peculiarities and main tendencies of the transport network development in Ukraine were highlighted. The results the qualitative indicators of socio-economic development of Kharkiv region territorial communities study, was confirmed by the hypothesis that theÂ transport factor directly influences the quality of the population life of a certain territory, significantly increasing the level of social inclusion of its population. The results of the residentsâ€™ survey in terms of assessing the quality of life in the community and perceiving their inclusion in community development processes, taking into account the results of the groupings and organization, are representative for all communities of the state. The proposed approach of territorial communities clustering is based on four main indicators: population size, length of roads, area and revenues of the community budget, as well as the share of community territories in the total area ofÂ theÂ district. Two-parameter graphs were illustrated to generalize the characteristics of the communities distribution, which provide an ordered cumulative visualization based on the main indicators.Â Â